A method for camera pose estimation from object of a known shape - Kang, Dong-Joong; Ha, Jong-Eun; Jeong, Mun-Ho (SPRINGER-VERLAG BERLIN, 2006)
Pose estimation between cameras and object is a central element for computer vision and its applications. In this paper, we present an approach to solve the problem of estimating the camera 3-D location and orientation from a matched set of 3-D model and 2-D image features. We derive an error equation using roll-pitch-yaw angle to present the rotation matrix and directly calculate the partial derivatives of Jacobian matrix without use of numerical methods for estimation parameters from the nonlinear error equation. Because the proposed method does not use a numerical method to derive the partial derivatives, it is very fast and so adequate for real-time pose estimation and also insensitive to selection of initial values for solving the nonlinear equation. The method is proved from real image experiments and a comparison with a numerical estimation method is presented.
Keywords: RECOGNITION